Pendidikan Lingkungan Dalam Perspektif Islam: Telaah Konseptual dan Implementatif - Abd.Rahman (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the role of environmental education in raising ecological awareness and to identify the supporting and hindering factors in its implementation. Using a qualitative approach, data were collected through literature reviews, interviews, and observations at both formal and non-formal educational institutions. The findings indicate that environmental education plays a significant role in shaping environmentally friendly awareness and behavior among learners. It encourages a deeper understanding of ecological issues and fosters a sense of responsibility toward the environment. However, in practice, the implementation of environmental education still faces various challenges. The main obstacles identified include limited resources, a shortage of educators with specific competencies in environmental topics, and a lack of policy support from both government and educational institutions. On the other hand, practice-based learning methods—such as field activities, environmental projects, and collaborations with local communities—have proven more effective in enhancing active participation and engagement among students. The main contribution of this study is to provide insights into optimal strategies for the implementation of environmental education, along with recommendations for policymakers to improve its effectiveness through curriculum strengthening and innovative teaching methods. These findings also serve as a foundation for developing more contextual and applicable learning models. For future research, it is recommended to broaden the scope of the study by examining the effectiveness of environmental education in various socio-economic contexts and exploring the use of digital technologies in environmental learning.